The effect of complex teaching on sensory modeling of some offensive handball skills (International Journal of Psychosocial Rehabilitation, 2020)
The researchers adopted the experimental approach due to its appropriateness and the nature of the research. The research community consisted of second-stage students at the Faculty of Physical Education and Sports Science at Diyala University for the academic year 2018-2019 (213 students). The sample was chosen randomly by lottery (number 37). A student from one division is (b) among the people, who are (7) people, excluding Division (f) and Division (g) represented by the second-stage students, and the sample was divided into three experimental groups according to the sensory modeling scale, and parity between research groups In learning some offensive skills with handball, the subject teacher applied the curriculum using the combined teaching method according to the preference for modeling in the main section of the research groups. The educational curriculum took (14) educational units and (2) educational units for each group per week, and the time for the educational unit was (90) minutes. The special program used in the statistical fields and SPSS system was used to extract the data of the research.